(untitled) (Research, Society and Development, 2022)
Purpose: To assess the quality of evidence for the efficacy of manual therapy in improving hand function in relation to surgical decompression in women with CTS. Methodology: Seven electronic databases were searched to identify randomized controlled trials that compared the efficacy of exclusive manual therapies and surgical decompression in improving hand function in women with carpal tunnel syndrome. Quality assessment was conducted using the Cochrane risk of bias tool. The study was registered in PROSPERO under number CRD42018084250. Results: Two trials were identified and included in the review. The results of critical appraisal of quality was low risk of bias. Conclusion: Evidence suggest that manual therapy may have similarly effective in relation to surgery decompression in improving hand function in women with carpal tunnel syndrome. Future trials must assess the efficacy of manual therapies in different numbers of session looking for better results.